Pelatihan Praktikum Kimia Berbasis Konstektual Di SMAN 3 Kupang Timur - Tukan, Maria Benedikta; Faderina Komisia; Maria Aloisia Uron Leba; Monika Langkeru; Maria Inosensia Jeno; Claudia D.T. Samara (LPPM Universitas HKBP Nommensen, 2025)
As a partner school, SMAN 3 Kupang Tmur, which is located in Kupang Regency, NTT Province, has several problems experienced by teachers and students for chemistry subjects, namely limited and inadequate laboratory equipment, the need for very minimal and insufficient practical materials so that activities Practicums are very rarely carried out due to the very expensive cost of materials, the unavailability of good and clear practicum guides, limited time availability from teachers due to the absence of laboratory assistants, and also insufficient laboratory space. Seeing these obstacles, in this activity teachers and students need to be provided with introductory chemistry practical activities because through practical activities they can increase students' knowledge and can provide illustrations or introduce important concepts of chemistry, train students to improve their reasoning, imagination and thinking skills. rational in seeking the truth, training students to apply scientific attitudes such as curiosity, perseverance, thoroughness, caution, objectivity, in dealing with all problems so that they do not easily believe in something that is not certain to be true, and making students more active in thinking and acting in their efforts search for truth or evidence of a theory being studied. Seeing the problems above and remembering how important practicum activities are in learning chemistry, practicum activities in schools will continue. The result of this activity is an increase in laboratory management skills and process skills by the students of SMAN 3 East Kupang.